From Edessa to Urfa: the fortification of the citadel - Tonghini, Cristina (Archaeopress archaeology, 2021)
From Edessa to Urfa: the Fortification of the Citadel is the outcome of an archaeological research project focused on a specific monumental area in the city of Urfa: its citadel. Urfa is better known to the general reader by its ancient name, Edessa. Three seasons of fieldwork were carried out (2014-2016), concentrating on the study of the evidence preserved above ground and employing the methods of stratigraphic analysis to identify the building sequence of the citadel and to characterise the various building phases. Transformation of the relative sequence into absolute chronology depended primarily on inscriptions in situ, but also on typological elements (masonry type, decorative elements, specific architectural forms). Data from the written sources also contributed relevant information regarding the development of the fortification works and the establishment of an absolute sequence --